AQbD-enhanced green RP-UPLC-PDA methodology for quantification and forced degradation studies for omeprazole, amoxicillin, and rifabutin - S. P. Ashnah Baffinsha; Vijayageetha Ragupathi; Hemanth Kumar Chanduluru (BMC Chemistry)
Abstract The ternary combination like omeprazole (OMP), amoxicillin (AMX), and rifabutin (RFB) was approved by the FDA in November 2019 for combating Helicobacter pylori infections and ulcers caused by this infection. This study aims to develop and authenticate a robust and eco-friendly RP-UPLC technique aimed at the concurrent analysis of OMP, AMX, and RFB, following ICH guidelines, Analytical Quality by Design (AQbD), and green analytical chemistry (GAC) principles. The analysis used the Thermo C18 column (100 mm × 2.1 mm, 1.7 µm), ethanol, and formic acid solution (43:57) as mobile phase with a flow rate of 0.2 ml/min at 272 nm. The method was developed based on the ICH Q14 and validated according to ICH Q2(R1) followed by Forced degradation studies under various conditions. The method showed good linearity for OMP, AMX, and RFB, with coefficient of determination (r2) of 0.9995, 0.9993, and 0.9997, respectively. Precision studies indicated low %RSD values, confirming high reproducibility. Forced degradation studies confirmed the stability of the drugs for 30 min in acid, base, and redox reactions, and they were also stable for 6 h at 105 °C in dry conditions. GAPI assessment depicted a green and yellow pictogram, AGREE scored 0.85, BAGI scored 80, and RGB12 Whiteness Assessment Tool scored 97.5%. The developed RP-UPLC-PDA technique is robust and reliable for the concurrent quantification of the triple combination. It aligns with sustainability goals, enhancing the efficiency and environmental sustainability of pharmaceutical analysis, and setting a benchmark for future analytical methods.